Analyzing an evacuated tube solar water heating system using twin-nano/paraffin as phase change material. (2022) - Rinawa, Moti Lal; Anitha Selvasofia, S.D.; Manoj Kumar, P.; Subbiah, Ram; Saminathan, Rajasekaran; Singh, Manoj Kumar; Saravanakumar, P.T.; Infant Tony Brain, G.; Eswarlal, Vimal Kumar
Abstract: In this work, an effort has taken to improve the thermal storage capacity of the evacuated tube solar water heating (SWH) system by means of a new kind of twin-nano/paraffin as a thermal storage medium. Beforehand, the twin-nano/paraffin has been prepared by amalgamating 1% mass of twin-nanoparticles (comprising an equal quantity of SiO2 and CuO nanoparticles) within the paraffin. The experiments were performed in three cases, viz., without paraffin, with paraffin, and with twin-nano/paraffin under the real-time solar conditions on the clear sunny days. The thermal storage characteristics had been measured in terms of the hotness of available hot water in the storage tank during the second day morning. The experiment for the each case was performed for twenty four hours continuously from the first day morning to next morning. During the experiment, the water was drawn-off after twelve hours, i.e., at 6 p.m in the evening, so as to replicate the real-time hot water demand in households. The experiments proved that the integration of paraffin and further, twin-nano/paraffin enhanced the thermal storage capacity of the evacuated tube SWH, by improving the temperature of available hot water during the next morning. The results substantiated that the water temperature was augmented by 8.8 °C and 11.7 °C, respectively with paraffin and twin-nano/paraffin. The enhancement was noticed to be significantly higher for the case with twin-nano/paraffin.